Hypokalemic Quadriparesis: An Unusual Manifestation of Leptospirosis - Mahendran K.; Kannan R.; Lal D.V.; Rajiv G.; Rajendran K. (Journal of Clinical and Diagnostic Research, 2014)
We report a 46-year-old male who presented with fever and flaccid weakness of all four limbs due to Leptospirosis associated hypokalemia. Acute hypokalemic quadriparesis is an uncommon presentation of leptospirosis, not yet widely recognised. Renal potassium wasting occurs in Leptospirosis and subsequently, the development of hypokalemia leads to paralysis. The patient had kaliuresis due to leptospirosis which improved with antibiotics and potassium replacement.